2021
DOI: 10.1007/s13592-021-00878-2
|View full text |Cite
|
Sign up to set email alerts
|

Mite diversity is determined by the stingless bee host species

Abstract: Mites can establish ecologically mutualistic and/or commensal relationships with stingless bees. In the present study, we evaluated the acarine diversity associated with colonies of three stingless bee species (Melipona quadrifasciata quadrifasciata , Scaptotrigona bipunctata and Tetragonisca fiebrigi ) in seven localities of southern Brazil. A total of 1458 mites from 18 species/morphospecies were sampled. The colonies of Melipona q. quadrifasciata showed the highest richness of mites, but T. fiebrigi was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…For these reasons, likely in the present work, we are describing the behaviour of a different mite species with other kinds of roles and/or interactions. DaCosta et al 21 studied the mite diversity of three stingless bee species ( Melipona quadrifasciata quadrifasciata , Scaptotrigona bipunctata , and Tetragonisca fiebrigi ) in southern Brazil. The authors found that mite diversity is determined by stingless bee host species and varies according to the areas of sampling.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, likely in the present work, we are describing the behaviour of a different mite species with other kinds of roles and/or interactions. DaCosta et al 21 studied the mite diversity of three stingless bee species ( Melipona quadrifasciata quadrifasciata , Scaptotrigona bipunctata , and Tetragonisca fiebrigi ) in southern Brazil. The authors found that mite diversity is determined by stingless bee host species and varies according to the areas of sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Although some mite species are associated with Meliponini (Fain & Fletchmann, 1985;Da-Costa et al, 2021), the goal of this work is to report the genus Leptus as a parasite in stingless bees.…”
Section: Introductionmentioning
confidence: 99%
“…Em virtude da densidade populacional e tamanho de suas colônias, os seus ninhos mantêm um microambiente ideal para o desenvolvimento de vários inquilinos, pois têm grande estoque de pólen e néctar, um controle térmico eficiente e manutenção de umidade (Viana et al, 2015). Portanto, suas colmeias são abrigo para outros organismos que se associam para usufruir dos recursos presentes, podendo estes ser benéficos e mutualistas, maléficos ou ainda com efeitos da interação não investigados (Nogueira-Neto, 1997;Coletto-Silva, 2005;Klimov et al, 2007;Da-Costa et al, 2021).…”
Section: -Introduçãounclassified